FAKTOR DETERMINAN YANG MEMPENGARUHI KEJADIAN UNMET NEED KB PADA PASANGAN USIA SUBUR DI KELURAHAN CAMPAGO IPUAH KECAMATAN MANDIANGIN KOTO SELAYAN KOTA BUKITTINGGI TAHUN 2018 - Nentien Destri, Debby Yolanda, (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
In Indonesia during 2015 the use of contraceptive tools has decreased drastically.Decrease in the use of contraceptives in Indonesia caused by increasing unmet need.Unmet need affects the increase of population and also affects health problems. Manyfactors that influence the incidence of unmet need include age and number of children, age,income, previous contraceptive failure, number of children. Therefore this study aims toanalyze the determinant factors associated with the incidence of Unmet Need KB incouples of childbearing age. This type of research is quantitative research using analyticalsurvey method with retrospective approach. The population in this study were all couplesof childbearing age in Kampago Ipuah urban village. The sample size in this study wascalculated using the formula with the finite population. The sample required in thisresearch is 178 people data collection using primary data through interview. This studyanalyzed the data that have been obtained through multivariate test.The result of thisresearch indicate that affectingfactor of unmet need family planning are age with p value0,000 (p<0,05) and number of children with p value 0,000 (p<0,05). According to result ofmultiple regression test,we get the determinant factor that affecting unmet needis age withOR value of age (0,135). Recomended to respondent to more know the effect if not usefamily planning, and for health personnel family planning to improve the health personnelfamily planning in counseling, hopefully it can to reduce the unmet need.Keywords: Unmet Need, Couples of childbearing age, family planning